Low Dose Dopamine Prevents End Organ Damage in Experimentally Induced Pancreatitis - Kaya, E; Arslan, A; Aliyazicioglu, Y; Guven, H; Aydin, O; Ozkan, K (H G E Update Medical Publishing S A, 2005)
Background/Aims: End organ damage due to microcirculatory failure plays an important role in the pathogenesis of acute pancreatitis (AP). The aim of this study was to investigate whether dopamine, a vasoactive agent, is beneficial in the prevention of local and systemic injury in acute pancreatitis. Methodology: Pancreatitis was induced in rats with 5% Na-taurocolic acid infusion into the pancreatic duct. Rats were resuscitated for four hours with saline in the pancreatitis group (P), lactated ringer's (LR) solution in the LR group and low dose dopamine (5 mu g/kg/min) + LR in the D-LR group. The sham group (S) underwent pancreatic duct cannulation only. Rectal temperature (RT) and mean arterial pressure (MAP) were monitored throughout the experiment. Blood samples for amylase, lipase, WBC and blood gas analysis were taken at baseline and at the end of the study. All rats were sacrificed at the 4th hour and pancreatic and lung tissues were removed for histopathological examination and tissue myeloperoxidase (MPO) activity. Results: MAP was lower in the P and LR groups than the sham and the D-LR groups. RT was higher in P and LR groups than the sham and the D-LR groups. Base deficit was higher in the P group than the sham and the D-LR groups. The lung MPO activity was higher in the P group than all the others. Lung MPO activity that is closest to the sham was that of D-LR group's. The pancreatic MPO activity was found to be increased in the P and decreased in the LR groups. Conclusions: In this experimental model for AP, low dose dopamine + LR resuscitation attenuates the lung injury but not the local pancreatic injury.
Keywords: Pancreatitis; Dopamine; Lactated Ringer; Myeloperoxicase Activity